Beriman Secara Autentik: Memahami Allah di Tengah Bencana Pandemi Covid-19 - Paul Cakra (Institut Agama Kristen Negeri Toraja, 2020)
Abstract: The main focus of this paper is to explain with theologically the phenomenon of life (Covid-19) which has recently become the unrest of mankind because it attacks all walks of life indiscriminately and gives a broad impact in various sectors of life including religious fields so that humans are forced to live in abnormal conditions and